Effect of filler loading on mechanical properties of natural carbon black reinforced polymer composites. (2020) - Naik, Prajapati; Pradhan, Smitirupa; Sahoo, P.; Acharya, S.K.
Abstract: In this article, the study of mechanical and morphological properties of orange peel and carbon black material from orange peel/ polypropylene composites was carried out taking various filler loadings (0, 10, 20, 30 and 40 wt%). The new carbon black materials were developed from bio-waste (orange peel) material using the pyrolysis method at different carbonization temperature (400 °C and 600 °C). All the mechanical properties such as tensile strength, modulus of elasticity, flexural strength, flexural modulus, impact strength and hardness properties were investigated as per ASTM standard. The experimental results demonstrate that the mechanical properties of fabricated samples are enhanced by increasing the carbonization temperature and filler weight percentage. In addition, the scanning electron microscope results reveal that the void percentage and pull out of reinforcing material increases with increase of filler loading.